PRESCHOOL CHILDREN’S RESULTS IN MOVEMENT ABC TESTS: DIFFERENCES BETWEEN GIRLS AND BOYS IN MOVEMENT DEFICIT - Jelovčan, Giuliana; Zurc, Joca (Annales Kinesiologiae, 2016)
The aim of our study was to assess the children's motor skills on a sample of preschool children between the age of 4 and 5 (x = 4.44 ̅, SO = 0.46), using a checklist questionnaire and movement assessment battery for children. We wanted to know whether the examined sample shows any deficits in movement or any physical difficulties, as well as what are the differences in gender. The study included 100 children from three kindergartens on the Slovenian coastal region. We used the percentile norms for common evaluation of movement problems. The total score below 15 percentile which indicates movement problems, was determined in 27 % of children, of which 66.7% in girls and 33.3% in boys. Statistically significant gender difference was found in the skipping rope test (p = 0.005), where boys performed better (x ̅ = 0.21) than girls (̅ x = 1.08). The findings show a high incidence of movement difficulties in preschool children, as a quarter of children do not reach the expected level of motor development, thus, this indicates the suspected occurrence of developmental coordination disorder. Further research is needed in the field of movement ABC tests application and in the incidence of movement deficites on a representative sample. It ia also advisable to identify the factors that are associated with movement deviations in preschool children. In encouraging a child's motor developement a greater attention should be given to girls in particular. The results of the movement ABC tests needs to be considered from the perspective of the child's holistic development and their motivation to perform.